FACTORS OF CHANGES IN DEMAND FOR THE USE OF FREIGHT WAGONS JSC “UKRZALIZNYTSYA” (International Journal of Innovative Technologies in Economy, 2023)
Providing a freight car for use is an integral part of the service of organizing the transportation of goods by railway transport. More than 600 companies offer wagons for use on the rail freight market. The largest owner of freight cars is JSC “Ukrzaliznytsya”. The company currently owns more than half of the freight wagons that are being loaded. At the same time, customers order no more than 30% [1]. This shows that the demand for the company's freight wagons is currently low. This leads to loss of income. This situation is due to the influence of various external and internal factors. Their determination and analysis will allow to change the situation with the demand for the company's freight wagons.